Determination of risk factors of neonatal pneumonia - Choudhury, AM; Nargis, S; Mollah, AH; Kabir, LM; Sarkar, RN (Mymensingh Medical Journal, 2010)
Mymensingh Med J. 2010 Jul;19(3):323-9 The abstract of this article is available on the PubMed website